Darling Rose Gold - Wrobel, Stephanie (Berkley, 2020)
For the first eighteen years of her life, Rose Gold Watts believed she was seriously ill. She was allergic to everything, used a wheelchair and practically lived at the hospital. Neighbors did all they could, holding fundraisers and offering shoulders to cry on, but no matter how many doctors, tests, or surgeries, no one could figure out what was wrong with Rose Gold. Turns out her mom, Patty Watts, was just a really good liar. After serving five years in prison, Patty gets out with nowhere to go and begs her daughter to take her in. The entire community is shocked when Rose Gold says yes. Patty insists all she wants is to reconcile their differences. She says she's forgiven Rose Gold for turning her in and testifying against her. But Rose Gold knows her mother. Patty Watts always settles a score. Unfortunately for Patty, Rose Gold is no longer her weak little darling... And she's waited such a long time for her mother to come home.